A relational identity approach to study the antecedents of family supportive supervision - Escribano, Pablo I. (Frontiers in Psychology, 2022)
This research focuses on the antecedents of family supportive supervisor behaviors (FSSB)– the support from supervisors that can help employees manage their competing demands across work and nonwork domains. Drawing on theories of relational identity and self-construal, I conceptualize subordinates’ likeability (interpersonal abilities) and competence (task abilities) as antecedents of family supportive supervisor behaviors, and examine whether supervisors’ relational identification with subordinates mediates this relationship. In addition, I also examine the extent to which this mediation depends on the level of relational self-construal of supervisors. Data from 205 subordinates and 84 supervisors from a Chilean private bank and results support the hypothesized mediated moderation model. While supervisors’ relational identification with subordinates fully mediates the relationship between competence and family supportive supervisor behaviors, supervisors’ relational identification with subordinates partially mediates the relationship between subordinates’ likeability and family supportive supervisor behaviors. Further, supervisors’ relational identification with subordinates mediates the relationship between likeability and family supportive supervisor behaviors when supervisors’ relational self-construal is high to medium but not when it is low. Overall, this research offers a novel lens for better understanding subordinates as more than mere recipients of supervisory behaviors.